2007
DOI: 10.1038/sj.ki.5002085
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic glomerulonephritis in children in Southwestern Uganda

Abstract: Acute renal disease is common in sub-Saharan Africa, with high mortality. Its etiology is poorly understood; quartan malaria owing to Plasmodium malariae was implicated in previous series. Few previous studies have included histological data; furthermore, much of the literature pre-dates the human immunodeficiency virus (HIV) epidemic. We report prospective analysis of acute proteinuric renal disease in children in rural Uganda. Clinical and laboratory data are presented on 65 patients (aged 2-14 years, mean 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…More recent studies have also found IgA deposits in malaria-associated AKI, with resolution after the acute phase of the infection 21 , 22 , as illustrated in Figure 2 . Eosinophilic glomerulonephritis has also been found in children with P. falciparum infection 23 ( Figure 3 ). Electronic microscopy findings evidence the presence of electron-dense deposits in subendothelial and mesangial region, associated with the presence of granular, fibrilar and amorphous material.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…More recent studies have also found IgA deposits in malaria-associated AKI, with resolution after the acute phase of the infection 21 , 22 , as illustrated in Figure 2 . Eosinophilic glomerulonephritis has also been found in children with P. falciparum infection 23 ( Figure 3 ). Electronic microscopy findings evidence the presence of electron-dense deposits in subendothelial and mesangial region, associated with the presence of granular, fibrilar and amorphous material.…”
Section: Introductionmentioning
confidence: 89%
“…Reproduced by Walker et al . 23 , with permission. ©2007 Elsevier – The International Society of Nephrology …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporally, at least in responding to foreign antigens, Th17 cells act earlier in immune responses and over time convert to a mixed Th1/Th17 or Th1 phenotype (44). Th2 cells support eosinophils, important in allergic interstitial nephritis and in glomerular disease in sub-Saharan Africa (62). CD81 cells are cytotoxic, killing cells that express their cognate peptide with MHC class 1, but also secrete cytokines and may act in a proinflammatory manner (63).…”
Section: T Lymphocytes: Subsets Directing Immunity and Glomerular Dismentioning
confidence: 99%
“…Renal microcirculation blockade due to parasite erythrocytes sequestration play a central role in all aforementioned pathogenic factors of renal failure in falciparum malaria [8,12]. Unlike P. falciparum, P. malariae can cause chronic glomerulopathy that may relentlessly progress to end-stage renal disease, related to granular deposits through the endothelium with IgG, IgM, C3 and parasite antigens deposits [13][14][15].…”
Section: Introductionmentioning
confidence: 99%